A national study of personal accomplishment, burnout, and satisfaction with work–life integration among advance practice nurses relative to other workers. Issue 11 (23rd November 2021) - Dyrbye, Liselotte N.; West, Colin P.; Kelsey, Elizabeth A.; Gossard, Andrea A.; Satele, Daniel; Shanafelt, Tait
ABSTRACT: Background: There is a high prevalence of burnout among health care professionals, but little remains known about burnout and satisfaction with work–life integration (WLI) among advance practice nurses (APNs). Purpose: To evaluate burnout and satisfaction with WLI among APNs compared with other US workers. Methods: A national sample of APNs and a probability-based sample of US workers completed a survey that measured burnout and satisfaction with WLI. Results: Of the 976 (47%) APNs who completed the survey 64% had high personal accomplishment, 36.6% had symptoms of overall burnout, and 60.6% were satisfied with their WLI. In multivariable analysis, work hours (for each additional hour odds ratio [OR] 1.03, 95% confidence interval [CI] 1.02–1.04, p < .001) and working in an outpatient setting (overall p = .03; referent hospital: outpatient, OR 1.80, 95% CI 1.17–2.18; other/unknown, OR 1.41, 95% CI 0.90–2.22, p = .13) were independently associated with having higher odds of burnout. Work hours were also independently associated with lower odds of satisfaction with WLI (for each additional hour OR 0.94, 95% CI 0.94–0.95, p < .001). Advance practice nurses were not more likely to have burnout or have greater struggles with WLI than other workers. Implications for practice: Findings from this study suggest APNs have high levels of personal accomplishment and a favorable occupational health profile. Advance practice nurses do not appear at higher risk of burnout or dissatisfaction with WLI than other US workers.